انعكاسات مخرجات نظام المعلومات الاستراتيجي في تعزيز الريادة: دراسة حالة في المستشفيات الأهلية في أربيل / إقليم كردستان - يوسف، بسام عبدالرحمن; يحيى، نور زهير (جامعة تكريت - كلية الإدارة والاقتصاد, 2018)
The study addressed the problem of low readiness of the Strategic Information Systems in the investigated hospitals in to provide the necessary information for strategic decision-making, The objective of the research is Identify the constraints facing the users of the strategic information system to take leadership decisions, The current research seeks to identify the relationship between the outputs of the Strategic Information System and achieving entrepreneurship, A checklist including a set of themes related to the strategic information system and entrepreneurship was used in the study, In order to achieve this, the health sector was selected as the population of the study and was represented by 10 private hospitals,... A number of results have been achieved, notably it was found that the investigated hospitals use semi-automated methods of information storage and retrieval and they are lagging in using entrepreneurship dimensions. The research recommended that the management of hospitals adopt entrepreneurship dimensions such as creativity, proactivity, risk tolerance and use the Strategic Information System to overcome the difficulties that may be encountered by the decision maker by providing appropriate information to the decision-maker when making strategic decisions.
تمثلت مشكلة البحث بانخفاض مستوى جاهزية نظام المعلومات الاستراتيجي في المستشفيات المبحوثة لتقديم المعلومات اللازمة لاتخاذ القرارات الاستراتيجية، أما هدف البحث تمثل بتحديد المعوقات التي تواجه المستفيدين من نظام المعلومات الاستراتيجي لاتخاذ القرارات الريادية، إذ يسعى البحث الحالي للتعرف على علاقة مخرجات نظام المعلومات الاستراتيجي في تحقيق الريادة، وقد تم استخدام قائمة فحص تتضمن مجموعة من المحاور المتعلقة بنظام المعلومات الاستراتيجي والريادة، وبغية تحقيق ذلك فقد تم اختيار القطاع الصحي ممثلاً بعشر مستشفيات خاصة، وقد تم التوصل إلى مجموعة من النتائج كان من أبرزها اعتماد المستشفيات على الطريقة نصف المؤتمتة في خزن واسترجاع المعلومات، فضلا عن عدم اعتماد الأبعاد الريادية، وأوصى البحث على ضرورة اعتماد إدارة المستشفيات الأبعاد الريادية مثل الأبداع والاستباقية وتحمل المخاطر وغيرها، فضلاً عن محاولة التقليل من الصعوبات التي تواجه متخذ القرار وذلك عن طريق استخدام نظام المعلومات الاستراتيجي في تزويد المعلومات المناسبة لمتخذ القرار عند اتخاذ القرارات الاستراتيجية.
Keywords: نظم المعلومات الإدارية -- التخطيط الاستراتيجي -- إدارة المستشفيات -- العراق